Análise de desempenho e características de fundos de fundos multigestores do mercado Brasileiro no período de setembro/1998 a agosto/2007 - Assali,Nicolau Alfredo (2008)
This dissertation analyses the performance and features of some of the current Brazilian funds of funds, called multimanagers, as well as the performance of funds of funds as a result of the simulation of Brazilian funds portfolios that use several investment strategies known as multimarkets. The diversification through a multimarkets funds portfolio involves other variables beyond the traditional approach of mean-variance. The first part of this study presents the main features of the selected funds of funds and also describes more than the mean-variance, showing the third and fourth moments of the returns distribution. The second part uses the tool named Style Analysis (Sharpe, 1988) in order to determine the return exposure of each of the funds of funds of the sample to certain asset classes. In this study were chosen the following asset classes: Ibovespa, CDI, Dollar and IRF-M. Through the medium-variance approach, the third part of this study uses a tool known as the Portfolio Theory (Markowitz, 1952) as the minimum variance frontier, in order to evaluate the performance of each funds of funds in the given sample. The performance is evaluated on the comparison basis of the minimum variance frontier built from a benchmark portfolio (comprising two of the major Brazilian financial assets of low and high risk: CDI and Ibovespa, respectively) with another minimum variance frontier built from the addition of a fund of funds into the benchmark portfolio. The last part refers to simulations of multimarkets portfolio funds that allow the allocation of variable income in the portfolio and it also allows the use of leverage. The goal is to check through the return of the average values, variance, asymmetry and kurtosis, the efficiency of such funds as instruments of diversification. The outcomes show that the 32 multimanager funds of funds analyzed do not have normal return distribution and 29 ones present negative skewness behavior. The Style Analysis indicates high sensibility to CDI and IRF-M, and low sensibility to Ibovespa and Dollar, main financial market indexes. The majority of multimanager funds of funds improved the Minimum Variance Frontier when added to a reference portfolio (CDI + Ibovespa), in other words, there was a reduction on risk – return relation. The portfolio simulation indicates that in the last three years the multimarkets funds classified as Leveraged Variable Income has been more aggressive in the strategies due to the asymmetry behavior; however this kurtosis behavior indicates a position not too aggressive as well. So the construction of Funds portfolios that use several investment strategies should not be restraint to the mean-variance approach. It should also involve asymmetry, kurtosis and investor preferences.